Maternal and perinatal outcomes of dichorionic diamniotic twins in women after spontaneous and assisted conception. (August 2021) - Elfituri, Abdullatif; Bakker, Wouter; Viswanatha, Radhika; Robinson, Eliza; Jan, Haider; Ganapathy, Ramesh
Abstract: Objective: Twin pregnancies have been shown to be associated with numerous maternal and perinatal complications. Published data shows conflicting reports on whether assisted conception influences these risks. The purpose of this study was to assess the impact of mode of conception on maternal and perinatal outcomes of dichorionic diamniotic twin pregnancies. Study design : This was a large retrospective study of 497 women with dichorionic diamniotic twins that were conceived spontaneously or with assisted conception in a single centre over a 10-year period. Results: This study showed no significant difference in mode of delivery (OR 1.40 95% CI 0.88 – 2.24), need for admission to neonatal unit (OR 1.56 95% CI 0.88–2.77), or preterm births between dichorionic twin pregnancies conceived following assisted conception when compared to spontaneously conceived dichorionic twin pregnancies. Women who conceived twins by assisted conception that did not have an elective caesarean section were more likely to go into spontaneous labour than have an induction of labour (OR 0.54 95% CI 0.3 – 0.99). They also had a higher chance of having an estimated blood loss of more than 1L than women who conceived naturally (OR 1.70 95% CI 1.06 – 2.73). Conclusions: In the case of dichorionic twins, this study showed that assisted conception does not seem to be associated with adverse obstetric and perinatal outcomes when compared with spontaneous conception. These results should be considered reassuring to women undergoing assisted conception, and may assist clinicians when counselling patients for assisted conception treatment. Further research is needed to assess the impact of assisted conception on postpartum blood loss.